Characteristics of older cyclists with self-perceived needs for improvement in cycling competence: SiFAr trial - Keppner, Veronika; Sieber, Cornel; Freiberger, Ellen; Kob, Robert; Krumpoch, Sebastian; Siebentritt, Hanna (European Geriatric Medicine, 2023)
Background: Older cyclists are in great risk of being injured or killed in a traffic-related accident and their needs should find more consideration in safety guidelines, urban planning, and future intervention programs. Objective: The aim for this cross-sectional analysis was to comprehensively explore characteristics of community-dwelling cyclists aged 65 years and older with a self-perceived need to increase cycle competence. Methods: 118 older adults (mean age 73.3 ± 5.2 years, 61% women) performed a standardized cycle course representing specific cycling skills. Additionally, health and functional assessments were carried out and characteristics regarding demographic, health, falls, bicycle equipment/type and cycling biography/behavior were obtained. Results: The majority (67.8%) of this community-dwelling adults reported being unsafe when cycling and 41.3% had a bicycle fall in the past year. More than half of the participants showed at least one limitation in each of the measured cycling skills. Women significantly had more frequent limitations in four of the cycling skills measured (p ≤ 0.001) compared to men. While no significant differences were found for falls, health and functional characteristics, women and men differed significantly in terms of bicycle type, equipment, and perceived safety (p < 0.001). Conclusion: Limitations in cycling should be compensated by preventive bicycle training and a safe cycling infrastructure. Bicycle fit, the wearing of bicycle helmets and promotion of a sense of security while cycling can further reduce accident risk and must find recognition in safety guidelines. In addition, educational initiatives have to dismantle gender-related bicycle stereotypes.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Aging; Cycling; Cycling safety; e-bike; Older adults

Concern About Falling Is Associated With Gait Speed, Independently From Physical and Cognitive Function - Van Schooten, Kimberley S.; Freiberger, Ellen; Smitt, Myriam Sillevis; Keppner, Veronika; Sieber, Cornel; Lord, Stephen R.; Delbaere, Kim (Physical Therapy, 2019)
BACKGROUND: Higher levels of concern about falling in older people have been associated with slower walking speed and an increased risk of falls. However, it is unclear whether this relationship is independent or confounded by other fall risk factors, such as physical and cognitive function. OBJECTIVE: The aim of this study was to examine the effects of concern about falling on gait speed, adjusted for physiological fall risk and cognitive function. DESIGN: This was an observational, cross-sectional study. METHODS: A total of 204 community-dwelling older people who were 70 years old or older were recruited from 2 sites (Germany, n = 94; Australia, n = 110). Walking speed was measured over 6 m under 4 conditions: preferred speed, fast speed, speed while carrying a tray (functional dual task), and speed while answering a question (cognitive dual task). The Falls Efficacy Scale-International was used to assess concern about falling, the Physiological Profile Assessment was used to assess physiological fall risk, and the Digit Symbol Substitution Test and Trail Making Test were used to assess attention and executive function. RESULTS: Higher levels of concern about falling were associated with slower gait speed. Following adjustment for age, history of falls, and female gender and further adjustment for physical and cognitive function, the association between concern about falling and walking speed remained significant, with a considerable effect size (standardized ß = 0.18 ± 0.08; P = .037). LIMITATIONS: The use of walking speed as a sole measure of gait was a limitation of this study. CONCLUSIONS: Gait speed, especially under dual-task conditions, was affected by concern about falling. Concern about falling was the strongest predictor of gait speed under all 4 conditions and should be included in routine geriatric assessments.
EVALuna2:52984

Gait Variability of an older, sarcopen Risk Population depending on different Gait Conditions - Krumpoch, Sebastian; Reith, Veronika; Meyer, Christian; Sieber, Cornel; Freiberger, Ellen (SPRINGER, 2018)

Lack of Influence of Skeletal Muscle Mass on the Determination of the Risk of Falling of self-reliant elderly Persons with functional Limitations - Gotthardt, Susann; Franke, Anna; Auerswald, Tina; Kraska, Carolin; Mellou, Marina; Hofmann, Anne; Reith, Veronika; Freiberger, Ellen; Sieber, Cornel; Schöne, Daniel (SPRINGER, 2018)

Safe Cycling in Old Age (SiFAr) - A randomized controlled Intervention Trial - Siebentritt, Hanna; Keppner, Veronika; Krumpoch, Sebastian; Freiberger, Ellen; Kob, Robert (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

Safer cycling in older age (SiFAr): a protocol of a randomized controlled trial - Siebentritt, Hanna; Keppner, Veronika; Britting, Sabine; Kob, Robert; Rappl, Anja; Sieber, Cornel; Freiberger, Ellen (BMC Geriatrics, 2021)
Background: Cycling has positive effects on health and the proportion of older cyclists is rising. However, the risk for older adults to be injured or killed by a bicycle accident increases. The aim of the ongoing project “Safer Cycling in Older Age (SiFAr)” is to promote safer cycling in community-dwelling older adults with a structured, multi-component exercise training. Methods: SiFAr is a randomized, controlled trial with a duration of 3 months for the intervention and a 6–9 months follow-up. We address community-dwelling persons aged 65 years and older living in the area Nürnberg-Fürth-Erlangen (Germany) who are either 1) beginners with the e-bike or 2) feeling self-reported unsteadiness when cycling or 3) uptaking cycling after a longer break. Long-term, experienced cyclists without subjectively reported limitations or worries when cycling are excluded. Participants are either randomized 1:1 to an intervention group (IG; receiving multi-component exercise program related to cycling, MEPC) or an active control group (aCG; receiving health and bicycle-related presentations, HRP). The purpose of this study is to investigate if the cycling competence of the IG will improve compared to the aCG. The cycling competence as primary outcome is tested not blinded in a standardized cycle course prior and after the intervention period, which consists of variant tasks requiring motor and cognitive skills related to traffic situations in daily life. Additional assessments such as physical functioning, quality of life, fear of falling, questionnaires regarding cycling behavior are obtained. To investigate the primary objective, regression analyses with difference of errors in the cycling course as independent variable and group as dichotomous dependent variable adjusted for covariates (sex, bicycle type) will be performed. The trial design is described in the present manuscript, using the extended CONSORT checklist for reporting pragmatic trials. Discussion: Since there is a lack of cycling-related interventions for older people, SiFAr aims to evaluate a standardized intervention to enhance cycling safety. The results of the SiFAr trial could contribute to the implementation of an evaluated cycling course concept promoting mobility and independence of older adults. Trial registration: This study was registered with clinicaltrials.gov: NCT04362514 on April 27, 2020
CRIS-Team Scopus Importer:2021-10-29
Keywords: Aging; Cycle training; Cycling safety; E-bike; Mobility; Randomized controlled trial

Safer cycling in older age (SiFAr): effects of a multi-component cycle training. a randomized controlled trial - Keppner, Veronika; Krumpoch, Sebastian; Kob, Robert; Rappl, Anja; Sieber, Cornel; Freiberger, Ellen; Siebentritt, Hanna (BMC Geriatrics, 2023)
Background: The risk of older adults being injured or killed in a bicycle accident increases significantly due to the age-related decline of physical function. Therefore, targeted interventions for older adults to improve safe cycling competence (CC) are urgently needed. Methods: The “Safer Cycling in Older Age” (SiFAr) randomized controlled trial investigated if a progressive multi-component training program related to cycling improves CC of older adults. Between June 2020 and May 2022, 127 community-dwelling persons living in the area Nürnberg-Fürth-Erlangen, Germany aged 65 years and older were recruited, who are either (1) beginners with the e-bike or (2) feeling self-reported unsteadiness when cycling or (3) uptaking cycling after a longer break. Participants were either randomized 1:1 to an intervention group (IG; cycling exercise program, 8 sessions within 3 months) or an active control group (aCG; health recommendations). The CC as primary outcome was tested not blinded in a standardized cycle course prior and after the intervention period and after 6–9 months, which consists of variant tasks requiring skills related to daily traffic situations. Regression analyses with difference of errors in the cycling course as dependent variable and group as independent variable adjusted for covariates (gender, number of errors at baseline, bicycle type, age and cycled distance) were performed. Results: 96 participants (73.4 ± 5.1 years; 59.4% female) were analyzed for primary outcome. Compared to the aCG (n = 49), the IG (n = 47) made an average of 2.37 fewer errors in the cycle course after the 3 months intervention period (p = 0.004). People with more errors at baseline had higher potential for improvement (B=-0.38; p < 0.001). Women on average made 2.31 (p = 0.016) more errors than men, even after intervention. All other confounders had no significant effect on the difference in errors. The intervention effect was very stable until 6–9 months after the intervention (B=-3.07, p = 0.003), but decreased with a higher age at baseline in the adjusted model (B = 0.21, p = 0.0499). Conclusion: The SiFAr program increases cycling skills among older adults with self-perceived needs for improvement in CC and could easily be made available to a broad public due to its standardized structure and a train-the-trainer approach. Trial Registration: This study was registered with clinicaltrials.gov: NCT04362514 (27/04/2020), https://clinicaltrials.gov/ct2/show/NCT04362514.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Aging; Cycle training; Cycling safety; e-bike; Mobility; Randomized controlled trial

Sarcopenia and Physical fRailty IN older people: multi-componentT treatment strategies: Design and Method of the EU Study SPRINTT - Freiberger, Ellen; Schöne, Daniel; Franke, Anna; Gotthardt, Susann; Reith, Veronika; Rempe, Hanna; Sieber-Eckert, Gabrielle; Sieber, Cornel (Internist, 2018)